(untitled) (International Seven Journal of Health Research, 2024)
Acute pulmonary edema is a clinical entity with a variety of etiologies, and if not managed quickly, can have negative outcomes. Some of the patients who develop this condition have heart failure, which, once decompensated, leads to ventricular failure and increased pulmonary capillary pressure, causing alveolar flooding. The aim of this article is to report a clinical case of a patient who presented with acute pulmonary edema secondary to an acute myocardial infarction, a condition associated with communication difficulties between the team and the patient due to the patient’s communicative limitations.